Antibody‐Modified Reduced Graphene Oxide Films with Extreme Sensitivity to Circulating Tumor Cells. (1st October 2015) - Li, Yingying; Lu, Qihang; Liu, Hongliang; Wang, Jianfeng; Zhang, Pengchao; Liang, Huageng; Jiang, Lei; Wang, Shutao
Abstract : An antibody‐modified reduced graphene oxide (rGO) film with unexpected extreme sensitivity to circulating tumor cells (CTCs) is reported. The antibody‐modified rGO films efficiently capture CTCs from billions of blood cells and minimize the background of white blood cells, without complex microfluidic operations.